An Overall Ship Propulsion Model for Fuel Efficiency Study. (August 2015) - Zhao, Feiyang; Yang, Wenming; Tan, Woei Wan; Chou, Siaw Kiang; Yu, Wenbin
Abstract: An overall ship propulsion plant involving marine engine, propeller and ship dynamic model was presented in this work. The cycle mean value model was utilized to describe the operation process in engine dynamic, intake/exhaust and turbocharger system. The ship shafting system was modelled using the power balance and its efficiency. The predicted results of fuel consumption, engine delivered power and vessel speeds were tested with measured data under different engine response. The whole ship voyage model will be used to predict fuel consumption and exhaust emissions under different sailing conditions in further study.